CHLORELLA VULGARIS INFLUENCE IN AQAUCULTURE - Mirzaodilova Nasiba Abdimuminovna , Aslanova Mukhtaram Askarovna (Confrencea, 2023)
Chlorella vulgaris microalgae has acquired a wide range of applications in the last century. This plant variety is widespread around the world and requires minimal conditions for growth and development: water, light, temperature and dissolved micronutrients. C. vulgaris are intensively used to treat natural water resources and to remove various pollutants from wastewater. As an empirical phenomenon, the amino acids found in Chlorella vulgris in large quantities contribute to the formation of complex compounds with metal ions. Furthermore, the biomass of algae has a valuable nutritional composition and is used as a feed for marine habitats and, according to repeated studies, can improve fish immunity, disease resistance and stress tolerance